(untitled) (Journal of Mining and Metallurgy, Section B: Metallurgy, 2019)
A green process was developed to treat an off-grade gravity lead concentrate. The selective leaching of Mo from an off-grade gravity lead concentrate was investigated in Na2CO3 solution using air as an oxidant. The leaching behaviors of Mo and Pb were predicted by the thermodynamic phase diagrams of Pb-Mo-C-H2O system. The oxidation mechanisms of those sulfides in the off-grade gravity lead concentrate were confirmed by these methods of X-ray diffraction (XRD) and scanning electron microscopy/energy dispersive X-ray spectroscopy (SEM/EDS). The influence of operating factors on the leaching behaviors of Mo and Pb was studied including Na2CO3 concentration, liquid-to-solid ratio, temperature and leaching time. Under these optimum leaching conditions (Na2CO3 2 mol/L, leaching time 8 h, temperature 75 °C, air-flow rate 2.0 m3/h and L/S ratio of 10/1 mL/g), the extraction of Mo and Pb was up to 97.70 and 0.73 percent, respectively.